2011
DOI: 10.1158/0008-5472.can-10-2684
|View full text |Cite
|
Sign up to set email alerts
|

Cep63 Recruits Cdk1 to the Centrosome: Implications for Regulation of Mitotic Entry, Centrosome Amplification, and Genome Maintenance

Abstract: Centrosomes are central regulators of mitosis that are often amplified in cancer cells. Centrosomes function both as organizers of the mitotic spindle and as reaction centers to trigger activation of Cdk1 and G 2 /M transition in the cell cycle, but their functional organization remains incomplete. Recent proteomic studies have identified novel components of the human centrosome including Cep63, a protein of unknown function that Xenopus studies have implicated in mitotic spindle assembly and spindle inactivat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…EP300 and MAP3K3 are, respectively, involved in the TP53 and RAS singnal pathway, which plays an important role in the pathogenesis of lung cancer. CEP63 binds to and recruits Cdk1 to centrosomes, and thus regulates mitotic entry (14). Although the function of CADM2 remained elusive, it has been reported that CADM2 was recurrently disrupted in prostate cancer (15).…”
Section: Molecular Modeling Of Tp53mentioning
confidence: 99%
“…EP300 and MAP3K3 are, respectively, involved in the TP53 and RAS singnal pathway, which plays an important role in the pathogenesis of lung cancer. CEP63 binds to and recruits Cdk1 to centrosomes, and thus regulates mitotic entry (14). Although the function of CADM2 remained elusive, it has been reported that CADM2 was recurrently disrupted in prostate cancer (15).…”
Section: Molecular Modeling Of Tp53mentioning
confidence: 99%
“…In prophase, Cdk1 is recruited to centrosomes by Cep63 and activated by forming a complex with phosphorylated Cyclin B1 (15,16). The most intriguing process in prometaphase is the appropriately timed search and capture of chromosomes by spindles (17).…”
mentioning
confidence: 99%
“…In 2011, we published a characterization of the phenotypes of Cep63 downregulation and overexpression in human cells in Cancer Research (1). Recently, it was shown that several antibodies commonly used to detect Cdk1 cross-react with Cep152 (2).…”
mentioning
confidence: 99%
“…Significances were determined using the heteroscedastic, twotailed Student t test. A, U2OS cells were transfected with siRNA to luciferase (Luc) or Cep63, respectively, fixed after 72 hours, and immunostained for g-tubulin and Cdk1 as described earlier (1). For Cdk1 immunostaining, the antibodies indicated in parentheses were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation